Feasibility of modified endarterectomized aortic allograft for middle hepatic vein reconstruction in living donor liver transplantation: A retrospective cohort study. (October 2021) - Kwon, Jae Hyun; Jung, Dong-Hwan; Hwang, Shin; Kim, Ki-Hun; Ahn, Chul-Soo; Moon, Deok-Bog; Ha, Tae-Yong; Song, Gi-Won; Park, Gil-Chun; Yoon, Young-In; Lee, Sung-Gyu
Abstract: Background: Cryopreserved allografts and artificial vascular grafts were introduced to meet the increasing demand for adequate vascular substitutes for middle hepatic vein (MHV) reconstruction during living donor liver transplantation (LDLT). This study evaluated patency outcomes after engraftment of a modified endarterectomized aortic allograft (MEAA) without any additional patches. Methods: This retrospective double-arm study was conducted in single tertiary referral center between January 2015 and July 2018. Of 1, 047 adult patients who underwent single-graft LDLT with a modified right lobe (MRL), 111 patients who received grafts with MHV reconstruction using MEAA were selected. The control group comprised 434 patients who underwent MHV reconstruction using iliac vein allografts. The main outcome measure was the short-term patency of the MEAA. The secondary outcome was the incidence of graft-associated complications. Results: Clinically significant MHV stenoses requiring stenting occurred in 3 patients (2.7%) in the MEAA group and in 17 patients (3.9%) in the iliac vein group (P = 0.778). Three-month and one-year patency rates on Doppler ultrasonography and computed tomography were 88.5% and 54.0%, respectively, in the MEAA group and 84.0% and 42.2%, respectively, in the iliac vein group, indicating the superior patency outcomes with MEAA (P = 0.017). Conclusions: MHV reconstruction using MEAA during LDLT of a MRL graft is technically simple, achieves clinical outcomes comparable to iliac vein grafts, and is effective in expanding the allograft vessel pool for LDLT. Highlights: Successful middle hepatic vein reconstruction in living donor liver transplant is crucial. Modified endarterectomized aortic allograft as middle hepatic vein conduit is developed. Our novel biological material is technically simple and feasible with good patency.